What matters to you? Improving the adoption of shared decision-making for birth planning in women with chronic hypertension: a multicentre multiple methods study - Hannah Wilson; Heather Brown; Jane Sandall; Marcus Green; Joanna Girling; Lucy Chappell; Rebecca Whybrow; Louise Webster (BMJ Open)
Objective To explore the role of shared decision-making (SDM) in the implementation of evidence-based practice in women with chronic hypertension planning birth and investigate the barriers and the facilitators in the provision of antenatal care.Methods A multimethod multisite approach was used including case-note review (n=55) and structured observations (n=18) to assess the provision of third trimester antenatal care. The barriers and facilitators to implementation were identified from semistructured qualitative interviews with healthcare professionals (n=13) and pregnant women (n=14) using inductive thematic analysis. The findings were integrated and evaluated using the ‘Three Talk Model of Shared Decision-making’.Setting and participants Pregnant women with chronic hypertension, some with superimposed pre-eclampsia and their principal carers at three National Health Service hospital trusts.Results Healthcare professionals delivering care to pregnant women with high blood pressure were aligned with most communication practices (set out in the Calgary-Cambridge communication guide). Pregnant women with hypertension who described being engaged in shared decisions about birth developed a trusting relationship with their maternity team. Despite frequent caesarean section birth (52%) and early term birth (median gestation at delivery 38 weeks (IQR1 37 weeks, IQR3 39 weeks) identified by case-note review; integrated data (observations, case-note review and qualitative interviews) found pregnant women with high blood pressure were not regularly provided with personalised information based on what they would find helpful, encouraged to share their own thoughts or offered choice in relation to timing or mode of birth. Uncertainty regarding the evidence around optimal timing of birth was the main barrier identified by professionals. Facilitators included training for professionals in SDM, midwife-led antenatal classes for high-risk women and multiprofessional clinics.Conclusions Strategies to promote more widespread adoption of SDM are likely to improve the experiences of women with high blood pressure making decisions about childbirth.